HPLC-MS Methodology for R. carthamoides Extract Quality Evaluation: A Simultaneous Determination of Eight Bioactive Compounds - Kosović, Ema; Lino, Kevin [UNESP]; Kuchař, Martin (MDPI, 2022)
Classified as an adaptogen, Maral root (Rhaponticum carthamoides, Leuzea carthamoides) is a herb that has long been used in Siberian as well as Russian alternative medicine. With over 200 substances found, this plant is a great source of bioactive compounds which have significant beneficial effects on human health and physical enhancement. Simultaneous quantification of the eight most therapeutic and abundant substances, i.e., 20-hydroxyecdysone (20-HE), kaempferol, hesperetin, quercetin, chlorogenic acid, N-feruloyl serotonin, cynaropicrin, and tracheloside belonging to various groups, such as ecdysteroids, flavonoids, phenolics, sesquiterpenes, and lignans, was performed for the first time through validated HPLC-MS. The evaluated parameters for method validation showed excellent linearity with R2 higher than 0.996, stability under various environmental factors with % RSD ≤ 2%, and recovery between 97 and 103% for all the studied compounds. Other validation parameters including selectivity, sensitivity, and precision were found to be within the acceptance criteria. The results of the stability studies provide information on the best combination of conditions for sample handling and storage. Generally, for almost every compound, exposure to light and elevated temperature for 96 h led to degradation; nevertheless, the acidic environment was beneficial for most of them.
Keywords: bioactive compounds; method development; sample handling; stability study; validation